Alexander Hamilton and the growth of the new nation - Miller, John Chester, 1907-1991, author.
1 online resource (xviii, 660 pages).
Keywords: Probably no American statesman displayed more constructive imagination than did Alexander Hamilton. Prodigal of ideas, bursting with plans for diversifying the economy, and obsessed by a determination to make the United States a powerful nation under a centralized government, he left an imprint upon this country that time has not effaced. Alexander Hamilton and the Growth of the New Nation is the premier biography of Alexander Hamilton written by one of the foremost scholars of early American history. Hamilton's career was at times contradictory: born, in John Adams's words, the "bastard brat of a Scotch peddler," he rose to high social, political, and military position in the newly born country. He dreaded divisiveness, yet his strategies and actions aggravated political sectionalism. Miller weaves together the complex facets of Hamilton's life to make a vivid, absorbing biography.